2019
DOI: 10.1039/c8re00330k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, application and kinetic modeling of CeOx–Si–CoMo catalysts for the hydrodesulfurization of dibenzothiophene

Abstract: CeOx–Si–CoMo catalysts for efficient hydrodesulfurization (HDS) activity of dibenzothiophene: role of ceria in catalyst activity and product selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…In order to explore the adsorption kinetics of DBT with Si-MCM-41/SA porous hybrid membranes, the pseudo-second-order kinetic model [30,31] was used to fit and analyze the adsorption kinetic data. The pseudo-second order kinetic equation is as follows [32]:…”
Section: Figure 9 Effect Of Adsorption Time On Adsorption Capacitymentioning
confidence: 99%
“…In order to explore the adsorption kinetics of DBT with Si-MCM-41/SA porous hybrid membranes, the pseudo-second-order kinetic model [30,31] was used to fit and analyze the adsorption kinetic data. The pseudo-second order kinetic equation is as follows [32]:…”
Section: Figure 9 Effect Of Adsorption Time On Adsorption Capacitymentioning
confidence: 99%
“…[88] Mostly, the choice of active metals is based on the level of hydrotreating operation with Ni(Co)Mo(W) being used as a conventional and most popular active metals over six decades in a carrier-free or supported matrix due to low cost and availability. [89][90][91][92][93][94] Moreover, the conventional active has may be employed as sulfided monometallic composed of Mo or W, bimetallic (NiMo, CoMo, NiW, CoW), trimetallic (NiCoMo, NiMoW, CoMoW, NiCoW) and ternary or multicomponent active metals. [95][96][97][98][99][100][101] In addition, various landmarks of noble and other transition metals have been reported.…”
Section: Active Phasementioning
confidence: 99%
“…HDS active metals are usually referred to the active phase after sulfidation in a stream of sulfur containing precursor, with a few exception to metal‐free carbon catalysts [88] . Mostly, the choice of active metals is based on the level of hydrotreating operation with Ni(Co)Mo(W) being used as a conventional and most popular active metals over six decades in a carrier‐free or supported matrix due to low cost and availability [89–94] . Moreover, the conventional active has may be employed as sulfided monometallic composed of Mo or W, bimetallic (NiMo, CoMo, NiW, CoW), trimetallic (NiCoMo, NiMoW, CoMoW, NiCoW) and ternary or multicomponent active metals [95–101] .…”
Section: Active Phasementioning
confidence: 99%
“…Therefore, it is important to increase the interaction between the metal and supports by means of modification. It has been reported that the doping of titanium, cerium, and other heteroatoms into the mesoporous molecular sieve has enhanced the performance of the support. When using 2.5-wt %-ceria-modified SBA-15 support, the metal–support interaction, the dispersion of the active phase, and the acidity of the catalyst are all in the optimal range. Compared with the activity of the unmodified catalyst at the normal reaction temperature (350 °C), even at a lower reaction temperature (325 °C), the HDS performance of the Ce-modified catalyst can almost reach twice that of the former.…”
Section: Developments Of Ultradeep Hydrodesulfurization Catalystsmentioning
confidence: 99%